Identifying factors influencing the low-income community in urban slum settlements in South Sumatera, Indonesia - Suhel Suhel; Imam Asngari; Mardalena Mardalena; Ariodillah Hidayat; Abdul Bashir (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2021)
The study is identifying factors influencing the low-income community in urban slum settlements in South Sumatra. The data utilized is primary data is taken through surveys and in-depth interviews. The samples were taken from 115 respondents purposively in the three cities of Palembang, Prabumulih, and Pagar Alam that are receiving benefits from the KOTAKU Program. The methods utilized are descriptive qualitative and quantitative approaches by applying multiple regression models. This study's findings indicate that jointly the variables of education level, age, family members, income expectations, and work types significantly affect the low-income communities' income level. Likewise, partially the education level variables, the family members, income expectations, and types of work positively and significantly affect income level. In contrast, the age variable has a negative and significant effect on the low-income community's income level in urban slums of South Sumatra.